Mitochondrial Drugs for Alzheimer Disease - Bonda, David J. (Molecular Diversity Preservation International, 2009)
Therapeutic strategies for Alzheimer disease (AD) have yet to offer a disease-modifying effect to stop the debilitating progression of neurodegeneration and cognitive decline. Rather, treatments thus far are limited to agents that slow disease progression without halting it, and although much work towards a cure is underway, a greater understanding of disease etiology is certainly necessary for any such achievement. Mitochondria, as the centers of cellular metabolic activity and the primary generators of reactive oxidative species in the cell, received particular attention especially given that mitochondrial defects are known to contribute to cellular damage. Furthermore, as oxidative stress has come to the forefront of AD as a causal theory, and as mitochondrial damage is known to precede much of the hallmark pathologies of AD, it seems increasingly apparent that this metabolic organelle is ultimately responsible for much, if not all of disease pathogenesis. In this review, we review the role of neuronal mitochondria in the pathogenesis of AD and critically assess treatment strategies that utilize this upstream access point as a method for disease prevention. We suspect that, with a revived focus on mitochondrial repair and protection, an effective and realistic therapeutic agent can be successfully developed.